PROFIL KEMAMPUAN CALON GURU MATEMATIKA DALAM MENGEMBANGKAN PERANGKAT PEMBELAJARAN SELAMA MELAKSANAKAN MICRO TEACHING - Rusi Ulfa Hasanah; Tanti Jumaisyaroh Siregar (JURNAL TARBIYAH, 2022)
This study aims to describe the ability of prospective mathematics teachers in developing lesson plans during micro teaching activities. This study is a qualitative descriptive research equipped with quantitative data used to explain the findings that exist before the results of the study concluded in qualitative form. To obtain the data, the researchers conducted observations and assessments using assessment instrument sheets based on Permendikbud number 22 of 2016 against the lesson plan prepared by 34 prospective mathematics teachers UIN North Sumatra Medan during micro teaching activities and interviews. Assessment of the lesson plan is done by giving a score on each aspect of the component with a scale assessment of 3 that is fully appropriate, partially appropriate, and not appropriate. The assessment score of each RPP component is processed by descriptive statistics and then categorized according to quantitative data classification and converted into qualitative data of three categories, namely high, medium, and low categories. The results of this study indicate that the ability of prospective teachers of mathematics in preparing all components of the lesson plan reached a high category except on one component.